FORMATION OF INTELLECTUAL SKILLS IN JUNIOR STUDENTS IN THE PROCESS ARTISTIC DESIGN - L.H. Fedorova (Academy of Cognitive and Natural Sciences, 2022)
Forming intellectual ability demands special conditions which helps child to overcome stresses, overstrain, uneasness, schools, fears, connected with the process o f teaching which contributes to propitious climate for fitted developing of pupils personality in the primary school.